Effects of chronic betaine supplementation on performance in professional young soccer players during a competitive season: a double blind, randomized, placebo-controlled trial - Hadi Nobari; Jason M Cholewa; Alfonso Castillo-Rodríguez; Mehdi Kargarfard; Jorge Pérez-Gómez (Taylor & Francis Group, 2021)
Objective Various nutritional strategies are adopted for athletes to maintain and to improve performance during the competition season. Betaine may enhance performance during a competitive season by increasing the testosterone to cortisol ratio and reducing systemic inflammation. The aim of this study was to investigate the effect of betaine supplementation on the bio-motor abilities in young professional soccer players. Methods Twenty-nine young professional soccer players (age, 15.5±0.3 years) were matched by position and randomly assigned to one of two groups for 14 weeks: betaine (BG, 2 g/day; n=14) or placebo (PG n=15). Diet was standardized by a nutritionist, and measures of muscular power (countermovement jump: CMJ), change of direction: modified 5-0-5), acceleration (10 m sprint), sprint performance (30 m sprint time: SpT), muscular strength (leg press and bench press one repetition maximum: 1-RM), repeated sprint ability (running-based anaerobic sprint test: RAST), and aerobic capacity (30-15 intermittent fitness test) were assessed in the pre (P1), mid (P2) and post (P3) season over the course of 5 days. All subjects participated in one soccer match and five training sessions per week. Results Significant (p < 0.05) group x time interactions were found for maximal oxygen uptake (VO2max), anaerobic peak power, and muscular strength favoring BG at P2 and P3 compared to P1. There were meaningful (p < 0.05) group x time interactions for CMJ, SpT, and peak power during the RAST that favored the BG. Conclusions 14-week of betaine supplementation increased predicted 1-RM, VO2max, and repeated sprint ability performance in youth professional soccer players. Betaine supplementation seems to be a useful nutritional strategy to improve and to maintain performance during a competitive soccer season.